Epidemiology and Characteristics of Resistant Typhoidal Salmonella Strains Prevalent in Lafia, Nigeria - Ngolo, Jebes Lamini; Orole, Olukayode; Chuku, Aleruchi (IPTEK The Journal for Technology and Science, 2025)
Resistance to antibiotics by pathogens is a burden to disease management. The study characterized Salmonella species in patients with fever and determined their antibiotic susceptibility patterns in Dalhatu Araf Specialist Hospital Lafia, Nigeria. Faecal samples were collected from 400 patients, and Salmonella species were isolated. The isolates were rested against ten antibiotics to determine their multi-drug and extensively drug-resistant capabilities, after which molecular characterization was done. Male patients between the ages of 21 to 30 years had the highest prevalence of 17(44.7%) of the pathogen, and they were the most susceptible among those who regularly drank water from boreholes (19(50.0%)). Augmentin with 44(73.0%) Salmonella susceptibility was the most effective antibiotic, while gentamycin, ampicillin, chloramphenicol, and cotrimoxazole had the isolates obtaining resistance of 60(100%), 59(98.0%), 57(95.0%), and 56(93.4%) respectively. Only six of the 60 Salmonella isolates were not multidrug-resistant, while 25 were extensively drugresistant. Isolates S9 and S25 with staG genes were the only Salmonella typhi found in the study; others with ttr genes were of the Salmonella genera. The study concludes that the first-line antibiotics administered to patients with typhoid fever are no longer effective; hence, proactive measures should be put in place to surmount the observed challenge.